The role of balance scales in supporting productive thinking about equations among diverse learners. Issue 1 (2nd January 2022) - Stephens, Ana; Sung, Yewon; Strachota, Susanne; Torres, Ranza Veltri; Morton, Karisma; Gardiner, Angela Murphy; Blanton, Maria; Knuth, Eric; Stroud, Rena
ABSTRACT: This research focuses on ways in which balance scales mediate students' relational understandings of the equal sign. Participants included 21 Kindergarten–Grade 2 students who took part in an early algebra classroom intervention focused in part on developing a relational understanding of the equal sign through the use of balance scales. Students participated in pre-, mid- and post-intervention interviews in which they were asked to evaluate true-false equations and solve open number sentences. Students often worked with balance scales while solving these tasks. Interview analyses revealed several categories of affordances of these tools for supporting students' productive thinking about equations.